Direct Energy Extraction from Brown Macroalgae‐Derived Alginate by Gold Nanoparticles on Functionalized Carbon Nanotubes. Issue 1 (January 2014) - Hoa, Le Quynh; Yoshikawa, Hiroyuki; Saito, Masato; Ueda, Mitsuyoshi; Shibata, Toshiyuki; Tamiya, Eiichi
Abstract The front cover artwork for Issue 01/2014 is provided by the research group of Nano‐Bioengineering at the Department of Applied Physics, Osaka University (Japan). The image illustrates the concept of using gold nanoparticle‐decorated carbon nanotubes to directly electrochemically oxidize brown macroalgae derived‐alginate into valuable chemicals and simultaneously extract bioenergy. Read the full text of the article on page 135.